Nonlinear optical response of thermally stable perovskite for near-infrared optical modulator - Jiang Wang; Liang Xie; Jingjing Liu; Yuxuan Sun; Jinglong Xu; Jiacheng Li; Zhongying Zhang; Chengbing Qin; Liantuan Xiao; Guofeng Zhang; Yonggang Wang; Zhichun Yang; et al. (Journal of Materiomics)
Metal halide perovskite has generated significant attention due to its high optical absorption coefficient, the tunability of bandgap, and its solution processing properties, all of which have led to a range of applications including solar cells, photodetectors, light-emitting diodes and lasers. However, the material's application as an optical modulator for high-energy ultrafast lasers is still limited by its slow nonlinear optical response, low damage threshold and the inferior stability. Herein, we developed a saturable absorber (SA) with the thermally stable Cs0.15FA0.85PbI2.85Br0.15 perovskite thin films as an optical modulator towards the near-infrared nanosecond passively Q-switched Nd:YAG laser generation for the first time. The Cs0.15FA0.85PbI2.85Br0.15 perovskite SA optical modulator produced an exceptional nonlinear optical response with a notable modulation depth of 15.1%, an ultrashort recovery time of 52.46 ps, and a high optical damage threshold exceeding 275.9 mJ/cm2. Of further significance, it displayed an excellent operational stability, and when incorporated into the oscillator of the Nd:YAG laser, allowed for a stable operation of 166 ns pulse laser with a center wavelength of 1.06 μm. The findings provide a pathway for the employment of the Cs0.15FA0.85PbI2.85Br0.15 perovskite SA optical modulator in near-infrared ultrafast laser applications.